New scenarios, new proposals, new femele actors: Indigenous Graduate Woman and the Intercultural University of Veracruz - Olivera Rodríguez, Inés (2017)
This article discusses the emergence of new actors among graduate students in Mexico, specifically of indigenous graduate women, who are one of the results of an educational model that intends to question the prevailing developmental logic. It describes and analyzes the role of intercultural higher education policies as catalyst for an emerging professional profile that is having important impacts in building new family, community and regional relations. Through the discussion of these policies, their origins, limits and possibilities, this paper focuses on the specific proposal of the Universidad Veracruzana Intercultural (UVI). It also examines the life experiences of five UVI female graduates, and concentrates in one case in which her trajectory is compared to the life experiences of her own mother, grandmother and great-grandmother. Through these cases, the paper seeks to identify the ways in which the UVI contributes to the constitution of these new female actors.